La protection sociale et la lutte contre la pauvreté en Algérie - LABBANI, Ouafa (Journal of Human Sciences, 2014)
Additionally first the legislator be interested what in designating factions from destitute and the jobless, whether helpful intention for the benefit aids was the youths possessors of the projects and the contractors their and the different distinctions, agglomerated you related in the donated loans before the banks and the financial organizations or the exemptions and the reductions the tax commitments, or from some weak factions because of the age and the healthy case; On him intention of merging in normal life avowed the legislator relative to protection the old persons their and guarantee for they dignifying life under auspices of their families or in the specified organizations for their reception when necessary.